2023
DOI: 10.3390/fermentation9040395
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics as Potential Therapy in the Management of Non-Alcoholic Fatty Liver Disease (NAFLD)

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease, the prevalence of which has increased over the years. The management of this pathology is not clear, and a specific pharmacological drug that can treat NAFLD is not available. In this sense, efforts are focused on the potential use of compounds with a natural origin that can contribute to reversing hepatic steatosis. Supplementation with probiotics, live microorganisms, is a potential strategy for the management of NAFLD. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 109 publications
1
0
0
Order By: Relevance
“…The change in microbiome composition and the increase in probiotic strains of Lactobacillus and Lactococcus during the intervention showed that the intervention modified the gut microbiome and thus likely drives the effects on liver metabolism via the microbiomegut-liver axis. An increase in Lactobacillus and its negative correlation with ALT levels indicates that Lactobacillus plays an important role in attenuating the progression of MAFLD, as reported previously [46,47].…”
Section: Discussionsupporting
confidence: 78%
“…The change in microbiome composition and the increase in probiotic strains of Lactobacillus and Lactococcus during the intervention showed that the intervention modified the gut microbiome and thus likely drives the effects on liver metabolism via the microbiomegut-liver axis. An increase in Lactobacillus and its negative correlation with ALT levels indicates that Lactobacillus plays an important role in attenuating the progression of MAFLD, as reported previously [46,47].…”
Section: Discussionsupporting
confidence: 78%